Influence of Cash Waqf Literacy on the Interest in Waqf of the Young Generation: a Study on Students of IAIN Palangka Raya - Herdayani, Herdayani; Misra, Isra; Hasnita, Hasnita (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
the low level of literacy regarding waqf causes a person's interest in waqf to be low. More precisely, someone's involvement in waqf is still lacking. The aim of this research is to determine the influence of cash waqf literacy on students' interest in waqf. The method used in the research was interviews and distributing questionnaires in the form of Google Form to respondents. This research is a type of quantitative research. In analyzing the data the author used simple linear regression analysis, t test and coefficient of determination regression analysis. The number of respondents in this study was 71 people who took part in the endowment seminar. Based on the results of research conducted, it was found that cash waqf literacy has a relatively low influence on students' interest in waqf. There is a need for waqf practices and providing more in-depth information about waqf.